ANALISIS MUTU PELAYANAN DEPARTEMEN HOUSEKEEPING DI TRAVELODGE HOTEL BATAM - Safrizal; Wahyudi Ilham; Andri Wibowo (Puslitabmas Batam Tourism Polytecnic, 2022)
Hotel is a form of commercially managed accommodation, where not only facilities and products are provided but also provide the best service to impress guests during their stay at the hotel. This is because hotels are experiencing a very rapid development, so there is a lot of competition in this industry. The quality of service is very important because when the hotel is able to meet the expectations, desires and satisfaction of guests, then they will want to come back to the hotel. This research aims to analyze indicators of service quality, namely reliability, responsiveness, assurance, empathy, and tangible. In this study, the authors used a qualitative approach with descriptive methods in case studies with informants as many as 8 people. Data is obtained from informants using data collectors in the form of interview guidelines, observations and documentation, then analyzed. The results showed that indicators of reliability, responsiveness, assurance and empathy have been said to be good and meet the criteria. While tangible indicators for neatness of the room attendant must be considered and improved again. Of the five indicators of service quality, all must be considered, maintained and improved again so that the number of guests increases and makes guests become loyal to the services provided by Travelodge Batam hotel.